Investigating the role of oxygen and residence time in the torrefaction of empty fruit bunch - Mohamad Khairul Aiman, Mohd Fauzi; Hernaez, G. R.; Ruwaida, Abdul Rasid (Universiti Malaysia Pahang, 2024)
This research investigates the oxidative torrefaction of Empty Fruit Bunch (EFB) as a renewable energy source. EFB samples from the LCSB palm oil mill were torrefied at 250°C with residence times (RT) of 10, 20, and 30 minutes and oxygen concentrations (OC) of 0, 5, 15, and 21%. Each experiment was repeated three times. Visual observations indicated that the EFB colour darkens with increasing RT, particularly at 5% OC, where torrefaction was found to be optimal. Higher OCs of 15% and 21% led to combustion but were ineffective due to insufficient incineration. Mass yield decreased with increasing RT due to moisture and volatile loss. The torrefaction severity index (TSI) showed a linear increase in the enhancement factor with increasing TSI, while energy yield decreased as the enhancement factor exceeded mass yield. The optimal condition for torrefaction was identified as 5% OC and 30 minutes RT, balancing energy efficiency and mass retention.